Interference source single satellite location method based on movable antenna with spot beam - Xijian ZHONG; Gengxin ZHANG; Zhidong XIE (Dianxin kexue)
An interference source single satellite location method based on movable antenna with spot beam was proposed for GEO satellites.In this method,a mapping relationship between orientation of interference and antenna gain is first established with the function of antenna pattern.Equations were established to calculate the interference signal link combining the orientation information of center of movable spot beam and the intensity of interference signal which derived from moving the beam several times.The orientation of interference was obtained by solving the equations with the help of particle swarm optimization(PSO).Then the longitude and latitude of the interference source could be calculated,jointly considering the ephemeris and the information of the earth.We made a positioning simulation of the ground interference source with the proposed method.The results validate the effectiveness of this method.